2017
DOI: 10.1177/0363546517736767
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Anterior Closing Wedge Tibial Osteotomy on Anterior Cruciate Ligament Force and Knee Kinematics

Abstract: PTS-reducing osteotomy significantly decreased ACL force and reduced ATT for knee loads that did not include IT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
71
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 35 publications
7
71
0
2
Order By: Relevance
“…Micromotion at the posterior region in the wedge increased and led to increased posterior tibial slope. The ACL force increased when the posterior tibial slope increased and indicated good agreement with the results of the previous study in which PCL force decreased [50][51][52].…”
Section: Discussionsupporting
confidence: 89%
“…Micromotion at the posterior region in the wedge increased and led to increased posterior tibial slope. The ACL force increased when the posterior tibial slope increased and indicated good agreement with the results of the previous study in which PCL force decreased [50][51][52].…”
Section: Discussionsupporting
confidence: 89%
“… 4 , 5 , 8 This is because it has been reported that increased tibial slope is directly correlated to increased anterior tibial translation, and has been shown to increase the forces experienced by the native ACL. 1 , 3 , 9 , 10 Clinical studies have supported these biomechanical findings, because an increased tibial slope has been reported to increase the risk of ACL graft failure, namely those ≥12°. 4 , 5 , 8 In our experience, we find intraoperatively that solely decreasing tibial slope before the second-stage ACL revision surgery can independently reduce anterior tibial translation.…”
Section: Discussionmentioning
confidence: 86%
“…The associated findings of primary PCL injury in > 100 patients with a decreased tibial slope appears to be a unique clinical finding that has yet to be fully investigated in the current literature. Although the association of sagittal plane tibial slope and ACL injury has been well studied 5,14,18,29 , literature regarding the impact of decreased posterior tibial slope and its associated risk for primary PCL injury is limited. After high tibial osteotomy, studies have highlighted the effect of increasing posterior tibial slope and the resultant increase in knee stability of PCL deficient knees.…”
Section: Discussionmentioning
confidence: 99%
“…11,18,21 Increased posterior tibial slope has been reported to alter the kinematics of the knee joint by anteriorly shifting the resting position of the tibia and subsequently increasingly the in situ forces on the anterior cruciate ligament (ACL). 4,8,28,29 Furthermore, increased posterior tibial slope has been directly correlated to higher anterior tibial translation (ATT), predisposing patients to ACL injury. 6,8 In contrast, increased posterior tibial slope counteracts PTT and reduces the stress placed on the native PCL.…”
Section: Introductionmentioning
confidence: 99%